Age at Onset of Spinal Cord Injury is Associated with Increased Inpatient Care Needs, Reduced Independence at Discharge and a Higher Risk of Institutionalization after Primary Inpatient Rehabilitation - Patricia Keusen; Thierry Vuilliomenet; Manuela Friedli; Mario Widmer (Medical Journals Sweden, 2023)
Objective: To investigate the influence of age at onset of spinal cord injury on length of stay, inpatient therapy and nursing hours, independence at discharge and risk of institutionalization. Design: Retrospective cohort study. Participants: A total of 250 patients with a newly acquired traumatic or non-traumatic spinal cord injury undergoing primary inpatient rehabilitation in a Swiss spinal cord injury specialized clinic between 2017 and 2019. Methods: Multiple regression analysis was used to determine if age, in addition to clinical characteristics (co-morbidities, secondary complications and spinal cord injury severity), affects inpatient rehabilitation parameters (length of stay, daily nursing hours and daily therapy hours), independence at discharge (Spinal Cord Independence Measure III) and place of discharge (private residence vs institution). Results: Chronological age correlated with the number of co-morbidities and secondary complications. Older age was associated with increased daily nursing care and reduced independence at discharge. However, both were also influenced by co-morbidities, secondary complications and severity of spinal cord injury. Length of stay and daily therapy hours were age-independent. Odds for institutionalization after discharge increased significantly, by 1.03-fold per year of age. Conclusion: Age at onset of spinal cord injury predicted inpatient nursing care, independence at discharge and the risk of institutionalization after primary inpatient rehabilitation. Co-morbidities, secondary complications and severity of spinal cord injury were also important influencing factors. LAY ABSTRACT The age at which people have a spinal cord injury is increasing, and there has been a shift from traumatic towards more non-traumatic causes, particularly at an advanced age. The aim of this study was to determine the influence of age at onset of spinal cord injury on the inpatient rehabilitation process and on independence at discharge. A total of 250 patients, with a median age of 57.0 years, undergoing primary inpatient rehabilitation in a Swiss spinal cord injury specialized clinic were included in the study. Older age was associated with a higher number of co-morbidities and more secondary complications. Age significantly predicted daily nursing hours, but not length of stay or daily therapy hours. Moreover, older age was associated with reduced independence at discharge and increased the risk of institutionalization after discharge. In addition to age, co-morbidities, secondary complications and severity of spinal cord injury were important influencing factors.